The potential of exosomes from adipose-derived stromal-vascular fraction in Increasing Migration Activity of Human Dental Pulp Stromal Cells (in vitro study) - Sylva Dinie Alinda; Anggraini Margono; Indah Yulianto; Ike Dwi Maharti; Reizka Asadelia Rafmawan (Elsevier, 2024)
Background: Migration of dental pulp stromal cells (DPSCs) significantly responds to wound healing after pulp injury. Deriving from low compliance characteristics, pulp tissue regeneration is challenging and depends on the microenvironmental signals. Exosomes can maintain and carry bioactive proteins that are crucial in cell communication. Adipose tissue-derived stromal vascular fraction (AD-SVF), a heterogeneous group of progenitor cells, is a promising source of exosomes. Objective: Discover the impact of exosomes derived from an adipose-derived stromal-vascular fraction (AD-SVF Exo) on human dental pulp stromal cells (hDPSCs) migration. Methods: In-vitro design involving AD-SVF Exo applied to hDPSCs cultivated until 80% confluence and 3rd-4th passage. AD-SVF Exo isolation through size exclusion chromatography (SEC). The AD-SVF Exo was characterized using Nanoparticle Tracking Analysis (NTA) and flow cytometry assays. hDPSCs were exposed to AD-SVF Exo (0% as the control group, 0.1%, and 1% as the experimental group), subjected to a scratch wound assay, and observed at 6, 24, and 48 h. Results: hDPSCs cultured expressed mesenchymal stem cell mesenchymal stem cell (MSC) markers and formed loose colonies with characteristic spindle-shaped morphology. AD-SVF Exo consisted of marker proteins CD9 and CD63, and NTA measurement demonstrated a diameter of 103 ± 24 nm in diameter with 1,6 x 108 particles/ml. Based on scratch assay, hDPSCs migration activity improved by reduced wound area in experimental groups. Data analyzed utilizing the Friedman (p < 0.001), and Kruskal Wallis (p < 0.05) test indicated differences in wound area after exposure of 0.1 % and 1 % AD-SVF Exo and observed at 6, 24, and 48 h. Conclusion: According to the findings of this research, AD-SVF Exo successfully enhances the wound healing capabilities of hDPSCs by improved migration activity, with the highest result found in 0.1% AD-SVF Exo.